ANALISIS KELAYAKAN USAHA PEDAGANG BUAH DI PASAR TANJUNG SARI KECAMATAN SUKOMANUNGGAL KOTA SURABAYA - Pitoyo aji, Bayu; Joko Priyono (Nirta Learning Centre, 2025)
Abstrak. This research aims to evaluate the income and business viability of fruit traders at Tanjungsari Market in Sukomanunggal District, Surabaya, a micro, small, and medium enterprise (MSME) in the fruit trading sector, mostly managed by the local community. Data was collected through interviews, observations, and documentation using a qualitative approach with primary data from fruit trader informants. Tanjungsari Market is located in the western part of Surabaya, specifically in Sukomanunggal subdistrict. The informants’ characteristics include their age, education, and business experience. Financial analysis was conducted using the R/C Ratio, B/C Ratio, and ROI to assess revenue, costs, and income. The results show that revenue ranges from IDR 6,700,000 to IDR 8,900,000, costs from IDR 5,000,000 to IDR 8,000,000, and income between IDR 6,500,000 and IDR 11,500,000. The ratios indicate that the business is financially viable and has potential for growth.